2008
DOI: 10.1530/rep-07-0375
|View full text |Cite
|
Sign up to set email alerts
|

SPINKL, a Kazal-type serine protease inhibitor-like protein purified from mouse seminal vesicle fluid, is able to inhibit sperm capacitation

Abstract: We report a secreted serine protease inhibitor Kazal-type-like (SPINKL) protein. The SPINKL protein was purified from mouse seminal vesicle secretions through a series of steps, including ion-exchange chromatography on a diethylaminoethyl-Sephacel column, gel filtration on a Sephadex G-75 column, and ion-exchange HPLC on a Q strong anion exchange column. Further analysis identified several SPINKL proteins with various N-linked carbohydrates. The SPINKL protein has six conserved cysteine residues that are nearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 47 publications
0
43
0
Order By: Relevance
“…A proteinase inhibitor of seminal vesicle origin was shown to block sperm-zona binding and the acrosome reaction [53]. In addition, SPINKL, found mainly on the midpiece, is able to inhibit sperm capacitation [20]. In this study, we showed that SERPINE2, another sperm acrosome-binding protein, also exhibits the ability to inhibit sperm capacitation in vitro.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…A proteinase inhibitor of seminal vesicle origin was shown to block sperm-zona binding and the acrosome reaction [53]. In addition, SPINKL, found mainly on the midpiece, is able to inhibit sperm capacitation [20]. In this study, we showed that SERPINE2, another sperm acrosome-binding protein, also exhibits the ability to inhibit sperm capacitation in vitro.…”
Section: Discussionmentioning
confidence: 67%
“…Protein bands on the SDS gel were excised and subjected to in-gel digestion with trypsin following our previously described method [20]. In brief, the gel was washed in a solution of 50% (v/v) acetonitrile and 100 mM NH 4 HCO 3 and digested by trypsin overnight at 378C.…”
Section: Protein Identification By Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The first member of the SPINK family, human SPINK1 (mouse Spink3), also known as pancreatic secretory trypsin inhibitor was discovered by Kazal (12). Previous studies and our in silico searches indicate that at least 13 SPINK family members are expressed in diverse tissues (13)(14)(15)(16)(17)(18). SPINK2, the only SPINK family member expressed in testes, was first identified in humans (11,19); however, informa-tion on mouse Spink2 has not yet been reported.…”
mentioning
confidence: 86%
“…SPINKL, a Kazal-type serine protease inhibitor-like protein found in mouse seminal vesicle fluid, binds to sperm and enhances motility. In addition, SPINKL also suppresses BSA-stimulated sperm capacitation and block spermeoocyte interactions in vitro [18].…”
Section: Introductionmentioning
confidence: 95%